The Interplay of Diet, Genome, Metabolome, and Gut Microbiome in Cardiovascular Disease: A Narrative Review - Darooghegi Mofrad, Manije; Ahn, Seoeun; Chun, Ock K. (Current Medicinal Chemistry, 2025)
Introduction/ObjectiveThe responsiveness to dietary interventions is influenced by complex, multifactorial interactions among genetics, diet, lifestyle, gut microbiome, environmental factors, and clinical characteristics, such as the metabolic phenotype. Detailed metabolic and microbial phenotyping using large human datasets is essential for better understanding the link between diet, the gut microbiome, and host metabolism in cardiovascular diseases (CVD). This review provides an overview of the interplay between diet, genome, metabolome, and gut microbiome in CVD.MethodsA literature review was conducted using PubMed and Scopus databases to identify pertinent cohort studies published between January 2022 and May 2024. This review focused on English articles that assessed the interplay of diet, genome, metabolome, and gut microbiome in relation to CVD in humans.ResultsThis narrative review explored the role of single-omics technologies-genomics, metabolomics, and the gut microbiome-and multi-omics approaches to understand the molecular basis of the relationship between diet and CVD. Omics technologies enabled the identification of new genes, metabolites, and molecular mechanisms related to the association of diet and CVD. The multiple omics approaches allows for more detailed phenotyping, offering a broader perspective on how dietary factors influence CVD.ConclusionOmics approaches hold great potential for deciphering the intricate crosstalk between diet, genome, gut microbiome, and metabolome, as well as their roles in CVD. Although large-scale studies integrating multiple omics in CVD research are still limited, notable progress has been made in uncovering molecular mechanisms. These findings could guide the development of targeted dietary strategies and guidelines to prevent CVD.
Keywords: genome